Effect of artificial night lighting on the growth of loose head lettuce in hydroponic system - Chua, H.S.; Lai, Siew Wei; Sivajothi Paramasivam; Goh, T.T.; Gee, Chia Chen (Penerbit Universiti Kebangsaan Malaysia, 2020)
Supplemental LEDs lighting technology has been used as the promising lighting source in hydroponic cultures for sustainable production in urban agriculture. It could be the solution to address the growing concern about food safety, environmental impacts, bad weather, and efficient energy usage in agricultural production. In this study, the response of loose head lettuce toward the irradiance of the supplemental red-blue LED light with different power (Watt [W]) was investigated by comparing the treated lettuce with the lettuce cultured under only natural light. The lettuce plants were treated with red LED (640-660 nm) + blue LED (440-450 nm). The power output of the LEDs was specified to 3, 6, 9, 15, and 20 W. The lettuce plants were hydroponically cultured with 8 h red-blue LEDs light exposure (from 12 to 8 am) and 16 h without the red-blue LEDs light exposure (from 8 pm to 12 am) at average air temperatures of 31/28 ºC (day/ night) for 50 days (7 weeks). On the harvesting day, the average shoot heights of the lettuce that was treated with 3, 6, 9, 15, 20 LEDs and natural light were 25.00, 24.75, 20.75, 19.88, 17.63, and 12.63 cm, respectively. The lettuce that was exposed to the 3 W LEDs had the highest shoot height compared to those that were exposed to LEDs with other power outputs. The average fresh weights of the lettuce that was treated with 3, 6, 9, 15, 20 W LEDs and natural light were 27.25, 24.75, 21.25, 19.88, 18.38, and 15.75 g, respectively. The results showed that the fresh weight of the lettuce that was irradiated with 3 W LED light was significantly higher compared to the lettuce that was exposed to LEDs with other power outputs. Hence, it can be concluded that supplementary LEDs lighting technology can be used as an alternative lighting source to improve the growth of lettuce in hydroponic systems. Moreover, the use of 3 W LEDs in hydroponic systems could yield a higher shoot weight and fresh weight.